Damage Signaling by Extracellular Nucleotides: A Role for Cyclic Nucleotides in Elevating Cytosolic Free Calcium? - Sun, Jian; Ning, Youzheng; Wang, Limin; Wilkins, Katie A.; Davies, Julia M. (Frontiers in Plant Science, 2021)
Extracellular ATP (eATP) is now held to be a constitutive Damage Associated Molecular Pattern (DAMP) that is released by wounding, herbivory or pathogen attack. The concentration of eATP must be tightly regulated as either depletion or overload leads to cell death. In Arabidopsis thaliana, sensing of eATP is by two plasma membrane legume-like lectin serine-threonine receptor kinases (P2K1 and P2K2), although other receptors are postulated. The transcriptional response to eATP is dominated by wound- and defence-response genes. Wounding and pathogen attack can involve the cyclic nucleotides cyclic AMP (cAMP) and cyclic GMP (cGMP) which, in common with eATP, can increase cytosolic free Ca2+ as a second messenger. This Perspective on DAMP signalling by eATP considers the possibility that the eATP pathway involves production of cyclic nucleotides to promote opening of Cyclic Nucleotide Gated Channels and so elevates cytosolic free Ca2+. In silico analysis of P2K1 and P2K2 reveals putative adenylyl and guanylyl kinase sequences that are the hallmarks of “moonlighting” receptors capable of cAMP and cGMP production. Further, an Arabidopsis loss of function cngc mutant was found to have an impaired increase in cytosolic free Ca2+ in response to eATP. A link between eATP, cyclic nucleotides and Ca2+ signaling therefore appears credible.